Inquiries into the measurement of vapour permeability of permeable materials. (15th January 2016) - Vololonirina, Oly; Perrin, Bernard
Highlights: Measurement of vapour permeability with cup method. Application to three very permeable insulating materials: rockwool, polyurethane, under-roof screen. Influence of boundary conditions on the diffusion resistance. Values of apparent and real vapour permeability depending on the boundary conditions of test. Abstract: This paper focuses on the measurement of the apparent vapour permeability of three different insulating materials: rockwool, polyurethane (PUR), and under-roof screen, by means of the cup method. The objective is to determine the influence of different test parameters on the superficial exchanges that affect the methodology of the vapour diffusivity determination. The parameters that are varied are: thickness and area of the specimen, thickness of the air gap at the lower surface of the specimen, air velocity, cup height, and hygrometry inside and outside the cup. Recommendations are then given for measuring the vapour diffusivity of very permeable materials with such a method.